India: Education System and School to Work Transition - Sodhi, Joginder Singh [Verfasser] (My University, 2014)
"In view of the liberalisation and globalisation of the Indian economy, rapid changes witnessed in scientific and technological world and the general need to improve the quality of life, Indian government has realized that it is essential that school leavers acquire a higher level of knowledge and skills. Education has received an exceptional impetus with a threefold increase in its budget and the launch of a 'Skill Development Mission' to provide work oriented skills as well as linking education with the world of work by broad basing vocational education and training (VET) at the school level itself." This article deals with the Indian education system and thereby takes a closer look in how far the different educational and vocational streams are linked with each other and with the world of work. (Text excerpt, BIBB-Doku)
Keywords: S System beruflicher Bildung; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; I 2.3.4 Asien; Bildungssystem; Berufsbildung; Berufseinmündung; Beziehung Bildungssystem Beschäftigungssystem; Indien